2002
DOI: 10.1071/sr01023
|View full text |Cite
|
Sign up to set email alerts
|

A pedo-transfer function (PTF) for estimating soil bulk density from basic soil data and its comparison with existing PTFs

Abstract: Collection of non-destructive soil core samples for determination of bulk densities is costly, difficult, time- consuming, and often impractical. To overcome this difficulty, several attempts have been made in the past to estimate soil bulk densities through pedo-transfer functions (PTFs), requiring soil texture and organic carbon (OC) content data. Although many studies have shown that both organic carbon and texture predominantly determine soil bulk density, a majority of the PTFs developed so far are a fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
2
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(72 citation statements)
references
References 13 publications
4
58
2
2
Order By: Relevance
“…The prediction error of model III was between the SDPE values observed for models II and IV, but model III was found to overestimate D b values. Similar to what was observed in models II and IV, this different performance of model III, as suggested by Kaur et al (2002) andDe Vos et al (2005), indicates that published models should be used with care when applied in environments other than the one in which they were developed.…”
Section: Validation Of the Regression Modelsupporting
confidence: 76%
“…The prediction error of model III was between the SDPE values observed for models II and IV, but model III was found to overestimate D b values. Similar to what was observed in models II and IV, this different performance of model III, as suggested by Kaur et al (2002) andDe Vos et al (2005), indicates that published models should be used with care when applied in environments other than the one in which they were developed.…”
Section: Validation Of the Regression Modelsupporting
confidence: 76%
“…BD has been found to decrease with higher clay and clay-plus-silt contents which is in agreement with our result (Kaur et al, 2002;Benites et al, 2007;Reichert et al, 2009), whereas the effect of medium and coarse sand on BD varied among soils, regions and horizons (Calhoun et al, 2001;Kaur et al, 2002;De Vos et al, Cs, coarse sand; Ms, medium sand; Fs, fine sand.…”
Section: Effects Of Sampling Depth and Soil Components On Bd And DCsupporting
confidence: 82%
“…It has been frequently reported that the BD of high-C soils can be explained by the variation in C content, whereas soil texture has a major effect on the BD of low-C soils (Manrique and Jones, 1991;Kaur et al, 2002). Total N showed a negative relationship with BD and DC (Benites et al, 2007).…”
Section: Effects Of Sampling Depth and Soil Components On Bd And DCmentioning
confidence: 90%
“…Besides, rb values determined with small and large cylinders corresponded to the functions of Eschner et al (1957) and Rawls (1983), while those determined with medium cylinders corresponded to three of the selected PTFs (Leonaviciute, 2000;Dexter, 2004;Rawls et al, 2004). On the other hand, the selected PTFs showed large differences in performance when applied to the fine-textured MPC soil (Figure 4), where their poor aggregation was attributable to very limited predictive potential (R 2 ) of published rb PTFs, which poorly capture the soil property variability (Kaur et al, 2002). In fact, according to the Tukey-Kramer test, only rb values measured with the MCy and those obtained with the Leonaviciute (2000) function did not show significant differences.…”
Section: Resultsmentioning
confidence: 99%
“…Several authors (Kaur et al, 2002;De Vos et al, 2005) have concluded that existing PTFs display large differences in performance and should be used with care, especially when applied in environments other than those in which they were calibrated. The anomalous behavior of the published PTFs used in this study suggests that the mineralogy of the validation soil samples may have been different from that of the soils from which the PTFs were developed.…”
Section: Resultsmentioning
confidence: 99%